Systemic sclerodermia associated with chronic hepatitis. Case report - Misterska, Małgorzata; Szulczyńska-Gabor, Joanna; Helak, Alicja; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Systemic scleroderma is a chronic disorder, with unclear etiopathology, affecting not only the skin and the subcutaneous tissue but also other internal organs. In some cases the course of the disease is severe and may cause therapeutic problems. We present a case of a 43-year man, who had rapid progression of the disease, with the skin and the internal organs – including the liver – affected nearly simutaneously. Liver disorder found in association with scleroderma is considered to be rare.